Amplification through local critical behavior in the mammalian cochlea - Rodrigo G. Alonso; Francesco Gianoli; Brian Fabella; A. J. Hudspeth (Proceedings of the National Academy of Sciences, 2025)
Hearing hinges upon the ear’s ability to enhance its responsiveness by means of an energy-expending active process that amplifies the very mechanical inputs that it detects. This process is defined by four properties that, although seemingly unrelated, consistently occur together: amplification, sharp frequency tuning, compressive nonlinearity, and spontaneous otoacoustic emission. In nonmammal tetrapods, the active process is evident in individual hair cells. The hair bundles of the bullfrog, for example, exhibit all four attributes by operating near a Hopf bifurcation—a critical regime in which these properties naturally coalesce. In mammals, however, the delicate nature of the cochlea has restricted the evidence for an active process to studies in vivo, where it is generally attributed to the collective effort of the outer hair cells that energize the traveling wave along the cochlear spiral. As a result, the cellular mechanisms that underlie the properties of mammalian hearing remain contested, with uncertainty about whether criticality plays a role in the cochlea’s active process. Here we show that, when placed in a recording chamber that closely mimics the in vivo physiological environment, a segment of the mammalian cochlea ex vivo displays the features of the active process—amplification, frequency tuning, compressive nonlinearity, and the generation of distortion products. We show that this process operates locally, independently of traveling waves, and that the sensory epithelium achieves active amplification by operating near criticality at a Hopf bifurcation. The results reveal the existence of a unified biophysical principle that underlies auditory processing across species and even phyla.